2022
DOI: 10.1002/bse.3039
|View full text |Cite
|
Sign up to set email alerts
|

How environmental reputation and ethical behavior impact the relationship between environmental regulatory enforcement and environmental performance

Abstract: The paper investigates the nature of the relationship between environmental regulation enforcement (ERE) and environmental performance of small and medium-sized enterprises (SMEs). Drawing upon the institutional theory and a sample of 229 SMEs, the results indicate an inverted U-shaped relationship between ERE and environmental performance. In addition, we theorized and found that environmental reputation moderates the U-shaped relationship between ERE and environmental performance, such that the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Second, previous research has seldom investigated the environmental perspective of reputation (except Martín‐de Castro et al, 2020; Tran & Adomako, 2022) and has instead focused on the measurement of reputation. The findings here significantly advance current understandings of the relationship between green reputation and environmental performance, which is the central concern of green reputation research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, previous research has seldom investigated the environmental perspective of reputation (except Martín‐de Castro et al, 2020; Tran & Adomako, 2022) and has instead focused on the measurement of reputation. The findings here significantly advance current understandings of the relationship between green reputation and environmental performance, which is the central concern of green reputation research.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a firm's green reputation is based on its history of global green activity and, thus, is essential for building positive perceptions of its green activities. We thus define green reputation as the collective level of environmental credibility attributed to a firm's past and current actions—external and internal, market and non‐market—as perceived by its stakeholders (Tran & Adomako, 2022). Superior green reputation is both an important asset and a source of sustainability that provides advantages that lead to positive results in several domains, such as enhancing financial performance (Bergh et al, 2010), increasing strategic flexibility (Quintana‐García et al, 2021), and improving corporation image (Lange et al, 2011; Pfarrer et al, 2010).…”
Section: Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Previous studies have concluded that environmental regulations may promote (Meng et al, 2020), inhibit (Martínez-Zarzoso et al, 2019, or have a nonlinear effect (Tran and Adomako, 2022) on enterprises' entrepreneurial performances, but the impact of environmental regulations on the non-traditional entrepreneurial behaviors of new energy enterprises, which focus on energy renewable use and sustainable development goals, still needs to be further confirmed. In this paper, we explored the impact of incentive environmental regulation and command environmental regulation on the sustainable entrepreneurial performances of new energy enterprises, and we found that:…”
Section: Main Findingsmentioning
confidence: 96%
“…As an important force in the global combat against climate change, corporations have paid growing attention to its environmental footprints. The current literature identifies corporate environmental performance as an important value driver for two main reasons: (1) it helps the firm to avert the rising regulative pressures for internalizing negative externalities (Deephouse, 1996; Roxas & Coetzer, 2012; Tran & Adomako, 2022; Wang et al, 2018), and (2) it neutralizes the firm's normative pressures to meet stakeholders' expectations and sustain corporate reputation (Bansal & Clelland, 2004; Dangelico, 2015; De Miguel De Blas, 2020; Kolk, 2016; Nguyen & Adomako, 2021).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%